Is Heterotopic Ossification Associated With Surgical Approach in Total Hip Arthroplasty?. Issue 7 (1st April 2023) - Wilke, Benjamin K.; Guier, Christian; Applewhite, Andres; Garner, Hillary W.; Stanborough, Rupert O.; Spaulding, Aaron; Sebro, Ronnie A.
Abstract : Background: Although risk factors for heterotopic ossification (HO) have been defined, the effect from surgical approach is not fully understood. The primary objective of our study was to evaluate the effect that surgical approach has on the risk for developing severe HO after total hip arthroplasty (THA) and compare this with other known risk factors. We hypothesized that there would be no difference in HO formation based on the surgical approach. Methods: We retrospectively reviewed all patients who underwent primary THA at our hospital between March 2011 and March 2021. Patients with HO documented in the radiology reports were cross-referenced with our THA data set and manually reviewed to determine Brooker classification. Patient demographics, medical comorbidities, surgical details, and medication information were collected from the electronic medical record and compared. Results: Of 3, 427 patients who underwent THA, 677 (19.8%) developed HO postoperatively. A multivariable analysis confirmed that surgical approach was independently associated with increased odds for HO development. The anterolateral (odds ratio [OR], 3.43; P < 0.001) and posterior (OR, 2.24; P < 0.001) approaches had increased odds for developing HO compared with the direct anterior approach. However, only the anterolateral approach (OR, 1.85; P = 0.033) demonstrated an increased association with the development of severe HO (Brooker 3, 4) postoperatively. Conclusion: Although the use of the direct anterior approach had the lowest overall OR for developing HO after THA, this is likely only clinically notable when compared with the anterolateral approach. Level of evidence: III